Efficiency of a Combination of Pharmacological Treatment and Nondrug Interventions in Childhood Narcolepsy - Kacar Bayram, Ayşe; Per, Hüseyin; Ismailoğullari, Sevda; Canpolat, Mehmet; Gumus, Hakan; Aksu, Murat (Neuropediatrics, 2016)
Objective Narcolepsy is a chronic sleep disorder characterized by excessive daytime sleepiness, cataplexy, hypnagogic and/or hypnopompic hallucinations, and sleep paralysis. It is one of the most important causes of excessive daytime sleepiness in the pediatric population. The aim of this study is to present the clinical and laboratory findings, and treatment results of pediatric patients with narcolepsy.Materials and Methods We studied five unrelated consecutive children with narcolepsy, focusing on clinical and laboratory features, the therapy and outcome over the 33-month follow-up period.Results The study subjects included two boys and three girls. The mean age at diagnosis was 11.8 ± 3.3 years (range: 8–16 years). Three patients had cataplexy. There were no hypnagogic hallucinations and/or sleep paralysis in any patients. All patients were educated about sleep hygiene, appropriate nutrition, and regular exercise. Three patients were treated with modafinil, while two patients received methylphenidate. Sodium oxybate was added to existing treatment in patients with cataplexy. Cataplexy attacks did not respond well to the treatment in one patient; therefore intravenous immunoglobulin therapy was given.Conclusions Early diagnosis is important to help narcoleptic patients in improving their quality of life. A combination of pharmacological treatment and nondrug interventions can greatly improve children's clinical symptoms.
Keywords: narcolepsy; cataplexy; polysomnography; treatment; children